Clinical and dermoscopic features of melanocytic lesions on the face versus the external ear - Kränke, Teresa; Blum, Andreas; Schulter, Günter; Hänßle, Holger; Braun, Ralph; Giuffrida, Roberta; Hofmann-Wellenhof, Rainer (Dermatology practical & conceptual, 2021)
Citation: Clinical and dermoscopic features of melanocytic lesions on the face versus the external ear. Deinlein T, Blum A, Schulter G, Haenssle HA, Braun R, Giuffrida R, Hofmann-Wellenhof R. Dermatol Pract Concept. 2021; 11(4):e2021124. DOI: https://doi.org/10.5826/dpc.1104a124 - Accepted: April 6, 2021; Published: September 2021 - Copyright: 2021 Deinlein et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License BY-NC-4.0, which permits unrestricted noncommercial use, distribution, and reproduction in any medium, provided the original authors and source are credited. - Funding: None. - Competing interests: None. - Authorship: All authors have contributed significantly to this publication. - Corresponding author: Prof. Rainer Hofmann-Wellenhof, MD. Department of Dermatology, Medical University of Graz, Auenbruggerplatz 8, Graz, Austria. Email: rainer.hofmannmedunigraz.at
Gesehen am 20.01.2022